On a case of labial sacharomycosis - Ribeyro, Ramón E. (1918)
The study of mycotic diseases has been regarded with indifference between us. Apart from the interesting work Escomel on Blastomycosis, our literature no comments on this important issue. Yet the conditions caused by fungi have become of considerable importance in pathology. A number of conditions, arbitrarily considered arthritic, syphilis or tuberculosis, have a micósico origin; at the expense of fungi have enlarged the picture of our etiologic agents.